Studies: An Irish Quarterly Review; Reformation 500, vol. 106, no. 424 - Esswein, Benjamin (The sixteenth century journal, 2020)
The article reviews the special volume of the Jesuit scholarly periodical "Studies: An Irish Quarterly Review; Reformation 500," vol . 106, no . 424 (2017/18), edited by Bruce Bradley, dealing with topics of the Reformation in Ireland.